Conducted EMI of Switching Frequency Modulated Boost Converter - Stepins, Deniss (Electrical, Control and Communication Engineering, 2013)
In this paper conducted electromagnetic interference (EMI) of boost converter with switching frequency modulation (SFM) is theoretically analyzed in details. In the analysis line impedance stabilization network parameters, power inductor and input filtering capacitor parameters are taken into account. The analysis shows that the conducted EMI attenuation due to the use of SFM depends not only on modulation index as it is assumed in numerous research papers, but also on central switching frequency. Useful expressions to numerically calculate SFM boost converter conducted EMI spectrum and attenuation due to the use of triangular and sawtooth modulation waveforms are derived. Additionally experimental verification of the theoretical results is performed using a superheterodyne spectrum analyzer. Moreover a procedure for the choice of optimum SFM parameters (modulation waveform, frequency deviation and modulation frequency) to get maximum conducted EMI attenuation is proposed.